Evaluation of STAT1 and Wnt5a gene expression in gingival tissues of patients with periodontal disease. Issue 2 (15th October 2018) - Haftcheshmeh, Saeed Mohammadian; Mohammadi, Asadollah; Soltani, Arash; Momtazi‐Borojeni, Amir Abbas; Sattari, Mandana
Abstract: Periodontal disease is a common chronic inflammatory disease of the oral cavity. This disease occurs as a consequence of uncontrolled inflammatory immune responses against periodontopathic bacteria. Several studies have documented the proinflammatory roles of the Signal Transducer and Activator of Transcription 1 (STAT1) and Wnt5a in inflammatory diseases. However, there has been no detailed investigation of STAT1 and Wnt5a genes expression in periodontal disease. So, we aimed to evaluate the expressions of STAT1 and Wnt5a in patients with chronic and aggressive periodontitis and determine their correlation with clinical parameters. Three groups of subjects were enrolled including control (20 healthy individuals), chronic (25 patients), and aggressive periodontitis patients (25 patients). The expressions of STAT1 and Wnt5a were evaluated in gingival tissue samples using a Real‐time polymerase chain reactions assay. The expressions of STAT1 and Wnt5a were significantly upregulated in chronic and aggressive periodontitis compared with the healthy control. We also found that the expressions of STAT1 and Wnt5a increased in aggressive periodontitis compared with chronic periodontitis. In addition, there was the linear relationship between the expression of STAT1 and Wnt5a and the clinical parameters, including clinical attachment loss and periodontal pocket depth. A linear relationship between the expressions of Wnt5a and the clinical parameters was also identified. Taken together, our findings highlight the roles of STAT1 and Wnt5a in the pathogenesis of the periodontal inflammation, suggesting these molecules as valuable therapeutic targets. Abstract : The chronic and aggressive periodontitis have been found to be associated with the expression of inflammatory mediators, STAT1 and Wnt5a. The expression of STAT1 and Wnt5a genes were identified to be over‐expressed in the gingival tissue samples isolated from patients with chronic and aggressive periodontitis.